Pengaruh Media Sosial Instagram Terhadap Minat Baca Masyarakat (Studi Kasus di Akun @KOMUNITASPEMBACABUKU) - Febrianti, Siska; Sudiar, Nining; H, Rosman (Jurnal El-Pustaka, 2021)
This research is entitled The Effect of Instagram Social Media on People's Reading Interest (Case Study on the @komunitaspembacabuku account). The purpose of this study was to find out how the influence of Instagram social media on reading interest in the case study community on the Instagram account @komunitaspembacabuku. The method used in this research is a quantitative method with the type of case study research. Data collection techniques using questionnaires, observation, and documentation. The population in this study amounted to 24,300 followers with a sample of 100 respondents. Based on the results of data analysis, it can be seen that there is a simultaneous positive and significant effect between Instagram social media on people's reading interest (a case study on the Instagram account @komunitaspembacabuku) with a calculated f value of 53.474 > 3.938 or (f count > ftable) so that Ho is rejected and Ha accepted. based on the coefficient of determination of the Instagram social media variable (X) it affects people's reading interest (Y) by 35% while the remaining 65% is influenced by other factors not examined in this study.